Food and dietary patterns and multiple sclerosis: a case-control study in Belgrade (Serbia) (Italian Journal of Public Health, 2009)
Background: The aetiology of multiple sclerosis (MS) is unclear, but numerous studies suggest that differentexogenous factors can lead to the development of the disease in genetically susceptible individuals. Theobjective of this case-control study was to determine the role of food and dietary patterns in patients with MSin the population of Belgrade (Serbia).Methods: In this matched case-control study, we included 110 cases with definite MS according to McDonald’scriteria, in whom the onset symptoms occurred up to 2 years prior to the interview, who were followed-up atthe Institute of Neurology, Clinical Centre of Serbia, Belgrade. The identical number of controls from the sameinstitution, individually matched by sex, age and area of residence, was recruited from patients with variousnon-autoimmune neurological disorders. Dietary information was obtained by using a frequency historyapproach.Results: According to univariate conditional logistic regression analysis the following factors weresignificantly related to MS: body mass index (BMI) less than 25 (OR=2.2, p=0.009), frequent consumption ofbeef (OR=1.7, p=0.043), chicken (OR=2.0, p=0.045), meat of the lamb (OR=2.1, p=0.013), butter (OR=1.7,p=0.056) and ice-cream (OR=1.8, p=0.031), with dose-response relationship. Consumption of majority ofvarious fruit was more frequently reported by controls. According to multivariate conditional logisticregression analysis, BMI less than 25 (OR=2.3, p=0.008), consumption (weekly) of beef (OR=2.0, p=0.017)and butter (OR=1.9, p=0.027) was significantly related to MS, while regular consumption of cherry (OR=0.4,p=0.024) had protective role.Conclusions: This study might assist in potential defining of the dietary factors that could contribute to therisk of developing MS
Keywords: multiple sclerosis; food habits; dietary pattern; risk factors; case-control study